Book Review: Change By Design: How Design Thinking Transforms Organizations and Inspires Innovation full, written by Tim Brown, ISBN – 978-0-06-233738-2, Harper Business, 2009 - Singh, Shalini (European Journal of Applied Sciences, 2018)
N/A